A [11C] CO dispensing system for rapid screening of carbonylation reactions. (25th October 2018) - Van der Wildt, Berend; Shen, Bin; Chin, Frederick T.
Abstract : [ 11 C] CO is a highly versatile synthon that allows for labeling at carbonyl positions of many molecules by means of transition metal‐mediated carbonylation reactions. The intrinsic complexity of carbonylation reactions often requires tedious screening of reaction conditions for obtaining satisfying yields. Herein, a [ 11 C] CO dispending system for performing multiple reactions with a single batch of cyclotron‐produced [ 11 C]CO2 is described. This semiautomated setup allows for more rapid and efficient screening of reactions and reaction conditions compared with the traditional "one beam for one reaction" strategy. Abstract : [ 11 C] CO is a highly versatile synthon that allows for labeling at carbonyl positions of many molecules by means of transition metal‐mediated carbonylation reactions. Herein, a [ 11 C] CO dispending system for performing multiple reactions with a single batch of cyclotron‐produced [ 11 C]CO2 is described.